Relación entre el acceso a internet y el logro educativo en los principales distritos de Maynas 2017 2024 - Torres Segura, Cesar Augusto (2025)
This research analyzes the relationship between internet access and educational achievement in the four main districts of the province of Maynas (Iquitos, Punchana, San Juan Bautista and Belen) during the period 2017 2024. This is a quantitative study, at a correlational level and with a non experimental design of panel data, which included as a study population 32 annual statistical records on internet access and educational achievement obtained from ENAHO-INEI. The results revealed that, in Maynas, internet access has had significant improvements, going from 46.43% at 2017 to 79.87% at 2024. In addition, the existence of a moderate positive relationship between internet access and educational achievement was identified in the analyzed districts ( = 0.3633, = 0.041). Similarly, for every 1% increase in internet access, educational attainment in Maynas improves by 0.0026 points. However, the impact varies by district. In Belén, a strong and significant correlation was found ( = 0.7312, = 0.039), while in Iquitos, Punchana and San Juan Bautista the relationship was not significant, suggesting that other factors could influence educational performance.